2019
DOI: 10.1039/c9sc00385a
|View full text |Cite|
|
Sign up to set email alerts
|

Heterodinuclear zinc and magnesium catalysts for epoxide/CO2 ring opening copolymerizations

Abstract: Eight heterodinuclear catalysts comprising Zn(ii) and Mg(ii) metal centres show high activity and selectivity for CO2/epoxide ring-opening copolymerization. Detailed kinetic analyses are reported and a chain-shuttling mechanistic hypothesis proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
134
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 129 publications
(146 citation statements)
references
References 62 publications
10
134
2
Order By: Relevance
“…6,7,17 Indeed, some of us have already reported high activity dinuclear ROCOP catalysts which are effective at low pressures (1 bar) of CO 2 . [18][19][20][21] Here, a di-zinc catalyst is targeted that is straightforward to prepare and which shows a zeroth order in CO 2 pressure over the range 1-40 bar. 22,23 In pioneering earlier work, Thomas and co-workers demonstrated that N-carboxyanhydride ROP could be used to produce polypeptides and the released CO 2 was subsequently used to make cyclic carbonates via tandem catalysis.…”
mentioning
confidence: 99%
“…6,7,17 Indeed, some of us have already reported high activity dinuclear ROCOP catalysts which are effective at low pressures (1 bar) of CO 2 . [18][19][20][21] Here, a di-zinc catalyst is targeted that is straightforward to prepare and which shows a zeroth order in CO 2 pressure over the range 1-40 bar. 22,23 In pioneering earlier work, Thomas and co-workers demonstrated that N-carboxyanhydride ROP could be used to produce polypeptides and the released CO 2 was subsequently used to make cyclic carbonates via tandem catalysis.…”
mentioning
confidence: 99%
“…53 A recent investigation into analogous ZnMg catalysts showed that by applying carboxylate ligands, in place of halides, it was possible to significantly enhance turn-over-frequency values. 18 Nonetheless, in this series of catalysts complex 6, featuring a p-CF3 benzoate ligand, showed no discernible difference in rate or selectivity, but a slight decrease in ether linkages, compared with 4. Attempts to further substitute the two remaining chloride ligands in 6 with p-CF3 benzoate groups were unsuccessful and resulted in broad, complex NMR spectra.…”
Section: Resultsmentioning
confidence: 61%
“…Overall, it is quite clear that the activity values for these complexes are very low and particularly compared to leading catalysts in this field. 18,19,54,55 The Zn(II)Mg(II) catalyst shows a TOF of ∼78 h −1 and quantitative selectivity for carbonate linkages, under the same conditions (Table 1). Nonetheless, it is worth noting that the activities are in-line with other ( previously reported) Group 13 catalysts (Table 1).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations